Two‐Dimensional Spectra of Radar Returns from Sea: 1. Theoretical and Numerical Study of the Group Line. Issue 12 (11th December 2019) - Platzer, F.; Saillard, M.; Fabbro, V.
Abstract: The work presented here aims at interpreting the pattern observed at low frequencies in wavenumber‐frequency ( k, ω ) representations (dispersion diagrams) of radar returns from sea surface. This pattern is sometimes referred to as the "group line" in the literature and is supposed to result from the nonlinear behavior of the signal with respect to surface profile. To confirm this assumption, we have calculated the patterns generated by various nonlinear terms of second order in sea surface height. It is shown that the resolution in frequency of most data is not sufficient to allow for an accurate representation of the group line through an FFT. A methodology is proposed to define an average slope of the group line, which can be interpreted in terms of velocity. Key Points: Two‐dimensional spectra were extracted from radar returns from sea surface A pattern is observed at low frequencies in wavenumber‐frequency spectra The characteristics of this pattern have been explicitly linked to the spectrum of waves